Answer/Step-by-step explanation:
Using [tex] f(x) = 3x^2 - 8x + 2 [/tex], simply plug each value of x into the function to get f(x) values.
Thus, when x = -1
[tex] f(-1) = 3(-1)^2 - 8(-1) + 2 [/tex]
[tex] f(-1) = 3*1 + 8 + 2 = 3 + 8 + 2 [/tex]
[tex] f(-1) = 13 [/tex]
[tex] f(0) = 3(0)^2 - 8(0) + 2 [/tex]
[tex] f(0) = 0 - 0 + 2 = [/tex]
[tex] f(0) = 2 [/tex]
[tex] f(1) = 3(1)^2 - 8(1) + 2 [/tex]
[tex] f(1) = 3*1 - 8 + 2 = 3 - 8 + 2 [/tex]
[tex] f(1) = -3 [/tex]
[tex] f(2) = 3(2)^2 - 8(2) + 2 [/tex]
[tex] f(2) = 3*4 - 16 + 2 = 12 - 16 + 2 [/tex]
[tex] f(2) = -2 [/tex]
[tex] f(3) = 3(3)^2 - 8(3) + 2 [/tex]
[tex] f(3) = 3*9 - 24 + 2 = 27 - 24 + 2 [/tex]
[tex] f(3) = 5 [/tex]
The correct table for the function is the last option.